Computer-based ambulatory information systems: recent developments. - Anderson JG (Journal of Ambulatory Care Management, 2000)
This article updates the author's earlier review of some of the major computer-based ambulatory information systems and the literature evaluating their costs, benefits, effect on quality of care, and physician acceptance. The evidence suggests that computer-based information systems can increase access to clinical information, improve physician performance, enhance quality of care, and facilitate outcomes research review. In addition to presenting health information networks and clinical decision support systems such as reminder systems, drug ordering systems, and medical care management systems, the article describes applications of telemedicine and Web-based systems. It also discusses barriers to the widespread use of computer-based ambulatory information systems.